Ocena ryzyka projektów informatycznych - Bryndza, Joanna (Evaluation of information project risk, 2006)
Risk is present in every aspect of information project. The article introduces the phases of project risk management process: identification, evaluation, planning, ownership, prevention and monitoring. The author presents selected techniques which are useful in identification and evaluation phase. The author describes the model of project risk management process and the place of evaluation in this process. The main aim of the article is an introduction to the methods of evaluation: expert interviews, network analysis, decision tree and score methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 227-233